The effects of alpha tocopherol supplementation on monocyte function. Decreased lipid oxidation, interleukin 1 beta secretion, and monocyte adhesion to endothelium. - Devaraj, S (1996)
Low levels of alpha tocopherol are related to a higher incidence of cardiovascular disease and increased intake appears to afford protection against cardiovascular disease. In addition to decreasing LDL oxidation, alpha tocopherol may exert intracellular effects on cells crucial in atherogenesis, such as monocytes. Hence, the aim of this study was to test the effect of alpha tocopherol supplementation on monocyte function relevant to atherogenesis. Monocyte function was assessed in 21 healthy subjects at baseline, after 8 wk of supplementation with d-alpha tocopherol (1,200 IU/d) and after a 6-wk washout phase. The release of reactive oxygen species (superoxide anion, hydrogen peroxide), lipid oxidation, release of the potentially atherogenic cytokine, interleukin 1 beta, and monocyte-endothelial adhesion were studied in the resting state and after activation of the monocytes with lipopolysaccharide at 0, 8, and 14 wk. There was a 2.5-fold increase in plasma lipid-standardized and monocyte alpha tocopherol levels in the supplemented phase. After alpha tocopherol supplementation, there were significant decreases in release of reactive oxygen species, lipid oxidation, IL-1 beta secretion, and monocyte-endothelial cell adhesion, both in resting and activated cells compared with baseline and washout phases. Studies with the protein kinase C inhibitor, Calphostin C, suggest that the inhibition of reactive oxygen species release and lipid oxidation is due to an inhibition of protein kinase C activity by alpha tocopherol. Thus, this study provides novel evidence for an intracellular effect of alpha tocopherol in monocytes that is antiatherogenic.